Perancangan Sistem Inventory Untuk Stok Barang Herbisida Pada UD. Anugrah Jaya Tani Dengan Bahasa Pemrograman PHP Dan Database MYSQL - Dwana Abdi Juliantho; Billy Hendrik (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2023)
Advances in information and communication technology are increasing quickly in any direction to generate a lot of information technology and applications in various fields. In the information field technology, inventory systems are also needed to visualize them goods warehouse at UD. Anugrah Jaya Tani. UD. Anugrah Jaya Tani is one of them a stand selling various herbicides. The use of chemical herbicides is intended not to affect the plant but to influence growth weed. Therefore, selective herbicides or agents are needed effective in controlling weeds. Inventory systems are one enabling factor can also be developed using Internet resources. Internet is possible role in encouraging activities. The reason is due to inventory activity requires communication between parties regarding this issue. That The goal of using an inventory system that enables the main thing Align customer demand with available supply or control existing inventory. The results of this research are to determine the number of goods in inventory marketed, creating a system that is accessible to everyone and creating attractive consultation layout. Inventory is a storage place owned by a company exchanged or used for business activities. All items are summoned inventory system, depending on the type of activity of the company.